Heterogeneity in COVID-19 vaccine uptake within low-income minority communities: evidence from the watts neighborhood health study - Elizabeth Wong; Ying Liu; Victoria Shier; Ashlesha Datar (BMC, 2024)
Abstract Background The literature on disparities in COVID-19 vaccine uptake focuses primarily on the differences between White versus non-White individuals or differences by socioeconomic status. Much less is known about disparities in vaccine uptake within low-income, minority communities and its correlates. Methods This study investigates disparities in COVID-19 vaccination uptake within racial and ethnic minoritized communities with similar socioeconomic backgrounds and built environments, specifically focusing on Black-Hispanic disparities and disparities within the Hispanic community by country of origin. Data are analyzed from the fourth wave (June 2021- May 2022) of the Watts Neighborhood Health Study, a cohort study of public housing residents in south Los Angeles, CA. Linear probability models estimated the association between vaccine uptake and participants' race/ethnicity, sequentially adding controls for sociodemographic characteristics, health care access and insurance, prior infection, and attitudes towards COVID-19 vaccines. Differences in reasons for vaccination status by race/ethnicity were also tested. Results Mexican Hispanic and non-Mexican Hispanic participants were 31% points (95% CI: 0.21, 0.41, p < 0.001) and 44% points (95% CI: 0.32, 0.56, p < 0.001) more likely to be vaccinated than non-Hispanic Black participants, respectively. The disparity between Black and Hispanic participants was reduced by about 40% after controlling for attitudes towards COVID-19 vaccines. Among Hispanic participants, non-Mexican participants were 13% points (95% CI: 0.03, 0.24, p = 0.01) more likely to be vaccinated than Mexican participants, however, these differences were no longer significant after controlling for individual and household characteristics (β = 0.04, 95% CI: -0.07, 0.15, p = 0.44). Conclusion There are sizeable racial and ethnic COVID-19 vaccination disparities even within low-income and minoritized communities. Accounting for this heterogeneity and its correlates can be critically important for public health efforts to ensure vaccine equity.